2008
DOI: 10.1071/wf07092
|View full text |Cite
|
Sign up to set email alerts
|

Soil temperatures during autumn prescribed burning: implications for the germination of fire responsive species?

Abstract: Prescribed fire is a widely applied management tool in native forests. There have been concerns raised about the ecological impacts of prescribed fire on native flora. One aspect of the debate is the extent towhich prescribed fire heats the soil to levels reported to trigger germination in the soil seed banks.We used Thermochrons to test soil temperatures at 2 and 5 cm in prescribed burns in dry sclerophyll forests. Soil temperatures during the burns were generally low (<40•C) with less than 5% of sites being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 32 publications
4
43
0
Order By: Relevance
“…Furthermore, Penman & Towerton (2008) suggest that autumn prescribed burns rarely generate soil temperatures required for germination of a range of obligate-seeding species in Australia. As our burn was conducted in autumn and over a limited spatial scale it is possible that insufficient temperatures were reached to stimulate germination of seeds in the deeper soil layers at Finniss, compared to the summer wildfire on the Eyre Peninsula which was reported to stimulate the germination of several hundred A. pinguifolia seedlings (Pobke 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Penman & Towerton (2008) suggest that autumn prescribed burns rarely generate soil temperatures required for germination of a range of obligate-seeding species in Australia. As our burn was conducted in autumn and over a limited spatial scale it is possible that insufficient temperatures were reached to stimulate germination of seeds in the deeper soil layers at Finniss, compared to the summer wildfire on the Eyre Peninsula which was reported to stimulate the germination of several hundred A. pinguifolia seedlings (Pobke 2007).…”
Section: Discussionmentioning
confidence: 98%
“…In the southern Appalachians, Hubbard et al (2003) found that understory prescribed burning produced average soil temperatures at 1 cm and 2 cm depth of 59°C and 45°C, respectively; however, temperatures much greater than these averages were observed at some locations. Such spatial variation of soil temperature during prescribed fire was evaluated by Penman and Towerton (2008) in dry sclerophyll forests. At 2 cm depth, 57% of sensors remained below 40°C.…”
Section: Introductionmentioning
confidence: 99%
“…During the adult phase, individuals spend >99% of their time in the forest away from breeding areas (Penman et al, 2008c) and it is these areas that are more likely to burn during a low or high intensity fire (Penman et al, 2007a;Collins et al, 2013). Low-intensity fires are likely to result in low mortality of adult frogs, due to the fossorial nature of the species, and the patchiness (Penman et al, 2007a) and low soil heating associated with low-intensity fires (Penman et al, 2006b;Penman and Towerton, 2008). Conversely, high-intensity fires tend to result in greater adult mortality (Penman et al, 2004), as such fires are more homogenous and result in higher soil heating (Humphreys and Craig, 1981;Bradstock et al, 1992).…”
Section: Study Speciesmentioning
confidence: 98%
“…Modelled low-intensity fires were based on observations of prescribed fire that were patchy and resulted in low adult mortality (Penman et al, 2007a). Soil temperatures experienced in such fires are not sufficient to result in mortality for the majority of individuals in the fire area (Penman et al, 2006b;Penman and Towerton, 2008). In contrast, high-intensity fires result in greater heating of the soil (Humphreys and Craig, 1981;Bradstock et al, 1992), causing higher mortality in the adult population.…”
Section: Impacts Of Fire On Metapopulation Viabilitymentioning
confidence: 99%